Donor-derived cell-free DNA for detection of acute rejection in lung transplant recipients - Yavuz, Gökce; Walter, Julia; Hirv, Kaimo; Wachter, Oliver; Dick, Andrea; Kovacs, Julia; Zimmermann, Julia; Glueck, Olaf M.; Vorstandlechner, Maximilian; Samm, Nicole; Fertmann, Jan M.; Sienel, Wulf; et al. (Frontiers in Immunology, 2025)
IntroductionAcute rejection is a significant risk factor for developing chronic lung allograft dysfunction. Current monitoring tools, transbronchial biopsies and HLA antibody determination, have limitations in detecting acute rejection. This study aims to explore the potential utility of donor-derived cell-free DNA (ddcfDNA) as a non-invasive biomarker for detecting acute rejection in lung transplant recipients (LTR).MethodsWe developed a molecular method based on digital droplet PCR to determine the total amount and the proportion of ddcfDNA. Using blood samples collected sequentially post-transplant from a cohort of 81 LTR, we compared median levels of %ddcfDNA in patients with acute cellular rejection (ACR), antibody-mediated rejection (AMR), infection, or decline in pulmonary function (FEV1).ResultsMedian %ddcfDNA levels were significantly higher in groups with ACR (1.92% [0.70%, 2.30%], p=0.0006), AMR (1.27% [0.34%, 2.29%], p=0.0009), isolated lymphocytic bronchiolitis (0.54% [0.23%, 2.18%], p=0.03), and infection or prolonged ventilation over 30 days (0.50% [0.22%, 2.35%], p=0.005) versus stable allograft function group (0.26% [0.09%, 0.60%]). %ddcfDNA levels were also elevated in patients with FEV1 loss compared to those with stable or improving FEV1 after 12 months (1.98% vs. 1.36%, p=0.04). An optimal cut-off of 0.73% for %ddcfDNA was calculated to detect ACR and AMR with 80% specificity and 68% sensitivity.Discussion%ddcfDNA is a promising biomarker for identifying allograft injury due to acute rejection in LTR and could be a valuable tool for monitoring allograft health.